2016
DOI: 10.5604/17322693.1194612
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation markers are associated with metabolic syndrome and ventricular arrhythmia in patients with coronary artery disease

Abstract: WBC, CRP and IL-6 are strongly associated with components of the metabolic syndrome. Their strong association with life-threatening ventricular arrhythmia emphasizes the proarrhythmic role of inflammation in the increased cardiovascular risk of CAD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 0 publications
0
22
0
1
Order By: Relevance
“…7 A plethora of evidence confirmed the potency of members of family long PTX (PTX-3) in promoting atherosclerosis. 10,11 Up to the present, reduction of low-density lipoprotein, application of anticoagulant drugs, percutaneous coronary intervention, and coronary artery bypass surgery have been considered as routine therapies for atherosclerosis. 9 An increased level of IL-6 during atherosclerotic exacerbates the pathological outcomes, and reduction of this interleukin has been shown to yield therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 A plethora of evidence confirmed the potency of members of family long PTX (PTX-3) in promoting atherosclerosis. 10,11 Up to the present, reduction of low-density lipoprotein, application of anticoagulant drugs, percutaneous coronary intervention, and coronary artery bypass surgery have been considered as routine therapies for atherosclerosis. 9 An increased level of IL-6 during atherosclerotic exacerbates the pathological outcomes, and reduction of this interleukin has been shown to yield therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
“…9 An increased level of IL-6 during atherosclerotic exacerbates the pathological outcomes, and reduction of this interleukin has been shown to yield therapeutic effects. 10,11 Up to the present, reduction of low-density lipoprotein, application of anticoagulant drugs, percutaneous coronary intervention, and coronary artery bypass surgery have been considered as routine therapies for atherosclerosis. 12 In spite of these modulations, many attempts have been focused on the application of natural compound and alternative medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have found a significant association between inflammation and increased risk of malignant arrhythmias . Safranow et al demonstrated significantly higher levels of high‐sensitivity C‐reactive protein and interleukin‐6 levels in patients with coronary artery disease who experienced sustained VT and VF. Tung et al found that nearly 50% of patients with unexplained cardiomyopathy and VAs had ongoing focal myocardial inflammation on positron emission tomography/computed tomography.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have found a significant association between inflammation and increased risk of malignant arrhythmias. 29 Safranow et al 30 patients with chronic ICMP and found that these cells were not associated with an increased risk of arrhythmic events. The same was true for the MSCs, which were not associated with an increase in the arrhythmic events in a short-or long-term follow-up 33 and seemed to have a potential antiarrhythmic effect reported by Ramireddy et al 34 Skeletal myoblast therapy has shown pro-arrhythmia responses, which was documented in clinical studies but not in controlled trials.…”
mentioning
confidence: 99%
“…Another important pathophysiological mechanism of AMIinduced VAs is the activation of the immune system and the release of proinflammatory cytokines. 29,30 proinflammatory cardiac cytokines were significantly increased in the acute phase after AMI. 31 IL-18 and IL-1β, as members of the proinflammatory IL-1 cytokine family, play key roles in the development of cardiac dysfunction.…”
Section: Neuroimmune Response and Post-ami Vasmentioning
confidence: 93%